Recanalization of total aortoiliac occlusion via contralateral aortofemoral bypass graft - Mahmut Tuna Katırcıbaşı; Uğur Özkan (KARE Publishing, 2016)
Summary- Severe aortoiliac disease is traditionally treated with aortofemoral bypass (AFB). However, certain recurrent problems typically follow this type of treatment, problems which often require surgical intervention. Presently described is the endovascular recanalization of the native aortoiliac arteries in 2 patients who had undergone AFB. One patient with a history of aortounifemoral bypass graft had a newly emerged distal abdominal aorta and contralateral iliac artery occlusion as a result of progressive atherosclerosis. Another patient had thrombosis of the left limb of aortobifemoral bypass graft. In these patients, primary stenting was used as secondary treatment to recanalize aortoiliac occlusion. To our knowledge, the present are the first reported cases of such treatment.